Bridging Health and Urban Life: WHO’s Active Mobility Toolkit in the Context of Primary Health Care and Healthy Cities Approaches - Jafar Sadegh Tabrizi (Taṣvīr-i salāmat)
The WHO’s Promoting Walking and Cycling: A Toolkit of Policy Options (by Fiona Bull, Mariken Leurs, and Juana Willumsen) offers a strategic, evidence-informed roadmap to embed walking and cycling into national and local policies, urban planning, and health promotion (1). It aligns closely with the core values of Primary Health Care (PHC), equity, community participation, intersectoral collaboration, and comprehensive, person-centered care, and strongly supports the Healthy Cities (HCs) movement, which promotes environments that enable health, safety, and well-being for all.The toolkit outlines seven key policy pillars, which I will focus on in relation to their alignment with PHC's values and principles and the objectives of the HCs initiative. 1. Integration into All Policies The toolkit advocates for embedding active mobility into transport, health, education, and urban planning strategies, confirming the "intersectoral collaboration" pillar of PHC and the HCs’ strategy of "Health in All Policies" (2,3). 2. Safe and Connected Infrastructure Designing walkable and bike-friendly networks promotes equity and accessibility, enabling underserved and vulnerable populations, such as children, the elderly, and those in low-income neighborhoods, to engage in physical activity and access services safely (4). 3. Inclusive and Safe Streets Streets that serve all users regardless of age, gender, or ability embody people-centered design, a key value in PHC, and promote inclusive urban development, a cornerstone of HCs (5,6). 4. Behavioral Change and Safety Culture Educational campaigns and road safety enforcement foster informed and empowered communities, supporting health literacy and community engagement, central to PHC and HCs approaches (7). 5. Prioritizing Active Mobility Reallocating space for walking and cycling reflects the PHC value of addressing social determinants of health (SDH) while enhancing urban equity and sustainability, which are key goals in the HCs agenda (8,9). 6. Integration with Public Transport Seamless mobility through multimodal integration enhances the continuity of care and access to PHC services while fostering sustainable and resilient urban ecosystems (10-12). 7. Promotion and Incentives Incentivizing walking and cycling through community-based programs promotes active citizen participation, one of the foundational elements of both PHC and HCs (13). Enablers and System Strengthening The toolkit highlights cross-sector governance, capacity building, legal support, financing, and community engagement as essential enablers. This aligns with systems thinking and whole-of-government and whole-of-society approaches, which are integral in both PHC revitalization and HCs development (14). Health Equity, Prevention, and Sustainability By promoting non-motorized transport, the toolkit contributes to disease prevention, climate resilience, and the advancement of Universal Health Coverage (UHC). It also reduces health inequities by making healthy choices accessible and safe for all, fulfilling PHC’s commitment to "health for all", UHC’s pledge of "leaving no one behind," and the HCs’ vision of creating "cities that are inclusive, safe, resilient, and sustainable" (SDG 11) (14). In conclusion, walking and cycling are not only transportation options; they serve as public health interventions, urban equity tools, and pathways to healthier cities. This WHO toolkit enables policymakers and communities to envision a bright future prioritizing people over cars in urban and health planning, a future fully aligned with PHC and HCs values.